Legal Education and Ethos of the Legal Profession in Hungary in the Civil Era - Gábor Schweitzer (Journal on European History of Law)
The paper is dealing with several aspects of legal education in Hungary in modern times and also reflects with the image of legal professions in Hungary from the age of enlightenment up to WW I. Legal education was considered to be one of the privileges of the churches before the period of enlightenment. The only university of Hungary, established at 1635 in Nagyszombat (today Trnava), was deeply influenced by the roman catholic church. Later on the significant protestant churches, the Calvinist and the Lutheran also established their so called legal academies. After the educational reform of Maria Theresia in 1777, several so called royal legal academies were also established in Hungary. In the period of dualism, after 1867 there were existing two universities and 10 legal academies in the country. The number of legal professionals among the Hungarian intelligence was traditionally high. The paper would like to answer why legal studies were so popular in that period. Citing memoirs and literary works also describes the changing images of different legal professions.